DEVELOPMENT AND PRINCIPLES OF INTERIOR DESIGN OF COMMERCIAL HALLS (Innovation in Woodworking Industry and Engineering design, 2026)
There are two types of functions with their own separate spaces in commercial halls – the service space and users’ space and two stakeholders – retailers and users. The objectives of the traders are focused on realization of goods and higher profits. The objectives of the users are associated with obtaining the best services at the lowest possible price. At the intersection point are the best strategy for the development of store and appropriate solutions of interiors.Design is one of the factor determining the success or failure of a shop. Today it is diffi-cult to identify the predominant feature in the image of commercial interior halls. Rather, one can speak of freedom of design expression and a series of tendencies, sometimes diametrical-ly opposed. Modern commercial halls are more than places for sale of goods. They are multi-sensory, interactive spaces that predispose and enable visitors to enjoy a comfortable, pleasant and relaxing environment.The paper examines the relations „seller–customer“ which determines the innovations in the structure of the interior space. The principles and trends in interior design of commercial halls are analyzed.